Psychometric evaluation of a national exam for clinical undergraduates - Han, Yuting; Jiang, Zhehan; Ouyang, Jinying; Xu, Lingling; Cai, Ting (Frontiers in Medicine, 2022)
Background: As a high-stake national-level examination administrated before students’ clerkship in China, the Standardized Competence Test for Clinical Medicine Undergraduates (SCTCMU) has received much attention from the relevant educational departments and society at large. Investigating SCTCMU’s validity and reliability is critical to the national healthcare profession education. Materials and Methods: Raw responses from SCTCMU, answered by 44332 examines of 4th-year undergraduate medical students on 300 multiple-choice items, were used to evaluate the quality of the exam via psychometric methods based on item response theory (IRT). The core assumptions and model-data fit of IRT models were evaluated, as well as the item properties and information functions. Results: The IRT models were fitted to the observed assessment data, where all the required assumptions were met. The IRT analysis showed that most items had acceptable psychometric properties, and the passing score was located close to the lowest measurement error computed from the model outcomes. Conclusions: The proposed modern psychometric method provides a practical and informative approach to calibrating and analyzing medical education assessments. This work showcases a realistic depiction of the IRT analysis process and therefore facilitates the work of applied researchers wanting to conduct, interpret, and report IRT analyses on medical assessments.